Private Infrastructure in Developing Countries : Lessons from Recent Experience - Gómez-Ibáñez, José A. (World Bank, Washington, DC, 2017)
Beginning in the late 1980s many developing countries turned to the private sector to provide basic infrastructure and utility services, such as highways, railroads, water, wastewater, electricity, gas, and telecommunications. Recent studies suggest that private involvement often benefited customers and reduced government fiscal problems without harming employees or enriching private providers excessively. There were enough high-profile failures, however, to discredit this reform in many quarters. Private involvement is likely to be more successful if it generates real efficiency gains rather than simply transferring costs among parties, if the systems of regulating the private companies are politically sensitive as well as technically competent, if the costs and constraints of private capital are not excessive, and if we are willing to adopt more modest and gradual schemes in difficult circumstances.